The Analysis of Students’ Learning Behavior In Isolated School of SMPN Satap Tojabi - Jamilah, Radhiyatul; Suryadi, Ray (Universitas Nurul Jadid, 2020)
The research aimed to analyze the student’s learning behavior in isolated school it was conducted in a qualitative approach in SMPN SatapTojabi, Babussalam, Lasusua Sub District, North Kolaka District, South east Sulawesi it was one of the isolated schools in North KolakaDistric, located on the mountain it was about eight kilometers from the level of land with no electricity, people still used solar power for doing an activity related to electricity. The subject was the third grade students in the academic year 2019 – 2020 with 14 students. The data was collected by using observation and interview. The result showed that they gave various behaviors, some of them were diligent, obedient, and polite some of them were lazy, always messing about, and denying. By giving positive reinforcement students were not eager to get the reward even though the teacher promised a special reward some of them were still not change the behaviors. These behavior such as did not do the homework on time, messing about when their friends start to work, do not come at class on time, and keep the class noisy. While by giving negative reinforcement some students still much less discipline and less concern about their education.